"Rhizosphere upheaval after tree cutting: Soil sugar flux and microbial behavior". Issue 1 (31st December 2022) - Widyati, Enny; Irianto, Ragil SB.; Susilo, Adi
ABSTRACT: Cutting trees removes all parts of their photosynthetic area, which affects rhizosphere assembly. However, information regarding the underground alteration process after tree cutting is insufficient. This study aimed to observe the fate of both root exudation and the rhizosphere microbial community following tree cutting. The study included 540 Calliandra calothyrsus Meissn. The experimental layout was a completely randomized block design with 3 blocks (cutting age) × 2 (cutting and not cutting) × 180 trees. Composite soil samples were collected from trees at 0–20 cm depth and stumps at 0, 2, 4, 8, and 12 weeks after cutting to observe the soil sugar content, pH, and functional group population. This study demonstrated that cutting reduced the flux of sugars below ground by 80% and caused rapid acidification (pH less than 5.0) of the soil. Total soil sugar depletion is presumed to be a mechanism by which C. calothyrsus survives and regrows after cutting. Sugar depletion affects significant shifts in the size and structure of the rhizosphere microbial community. Increasing soil acidity is another survival strategy to limit close competitor populations in the rhizosphere. This study confirms that C. calothyrsus is a proper species for developing in the coppice-harvesting-system (CHS) energy estate. Graphical abstract: uf0001